Perspectives in Support of the Narrative Turn in Pastoral Care - Demasure, K; Müller, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
Meaning is constructed or finds its expression in stories. This insight brought narrativity into prominence. The “narrative turn” in pastoral care will be discussed from three different supporting perspectives: • P. Ricœur’s hermeneutics • Social constructionism • Post-foundationalist practical theology How these perspectives support the narrative turn in pastoral care are considered and discussed after each section. At the end the authors reach the conclusion that the hermeneutics of Ricoeur, social constructionism and the postfoundationalist approach to theology are all part of one family. The article is concluded with the formulation of minimum requirements for Practical Theology in the domain of pastoral conversations as informed by the above mentioned three perspectives.